Análise da secagem convectiva de resíduo proveniente da fabricação de vinho - Dias, Gilmara Emanuela Leobet (2018)
Wine lees is a residue from the winemaking process that, without proper treatment, ends up polluting the environment. Thus, in view of this problem, this work has the objective of studying the drying of the lees from the wine industry. The main purpose is the thermal study of the waste aiming at the reduction of water volume and stability and quality of the organic compounds present for later use. First, the wine was physicochemically characterized by pH, turbidity, conductivity, chemical oxygen demand (COD), nitrogen, phosphorus, total solids and functional groups. After characterization, the factorial planning and preliminary tests were carried out to define drying methods and equipments. Drying experiments were carried out in oven drying with and without air circulation, drying by infrared heating and drying by forced convection using a wind tunnel in order to know the thermal behavior of the residue through the humidity on a dry basis and the mass flow of water. Experiments of Thermogravimetric Analysis (TGA), Differential Thermal Analysis (DTA), Differential Exploratory Calorimetry (DSC) were also carried out. The drying methods were analyzed comparatively for the mass flow of the residue and drying rate for different temperatures. From the factorial planning and the preliminary tests, it was verified how much the temperature and interaction between the temperature and the layer height exert a significant influence in the residue to be dried. Through the level curve and the response surfaces it was observed that the drying results have better results for temperatures lower than 85 °C. Thus, the drying methods studied were for temperatures close to 85 °C. Among these methods, oven drying with natural convection presented similar behavior when compared to infrared (IR) drying, with IR being slightly faster. At 60 °C, both had a drying time of 300 min. When comparing the forced convection oven (EC) with the wind tunnel test (TV), the drying kinetics were similar in time from 112 min to 60 °C. Thus, by comparing the methods, the evaporation process was more efficient by means of the forced flow (CF) in the drying process by natural convection (CN). In the tests carried out at 60 °C, it can be seen that CF drying had a much shorter drying time (110 min) compared to CN (325 min). In relation to the water flow, CF showed much higher values (0.46 g/s/m²) when compared to CN (0.21 g/s/m²). This behavior was repeated for the other temperatures studied. In this way, it was concluded that the drying processes adopted were suitable for drying the wine sludge, mainly by means of CF. It is also concluded, through the thermal analysis and the comparison of the residue with pure water, that there is an influence of the phenolic compounds present in the residue during the drying processes and, consequently, in the temperature.